2021
DOI: 10.3390/cancers13071560
|View full text |Cite
|
Sign up to set email alerts
|

Residual Disease in Glioma Recurrence: A Dangerous Liaison with Senescence

Abstract: With a dismally low median survival of less than two years after diagnosis, Glioblastoma (GBM) is the most lethal type of brain cancer. The standard-of-care of surgical resection, followed by DNA-damaging chemo-/radiotherapy, is often non-curative. In part, this is because individual cells close to the resection border remain alive and eventually undergo renewed proliferation. These residual, therapy-resistant cells lead to rapid recurrence, against which no effective treatment exists to date. Thus, new experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 174 publications
0
21
0
Order By: Relevance
“…Indeed, LAV-BPIFB4 treatment downregulates senescence both in cancer cells in vitro and in T lymphocytes from GBM patients, a key event which may support a dual activity of LAV-BPIFB4 in the cancer microenvironment. We demonstrated that LAV-BPIFB4 can specifically counterbalance the therapy-induced senescence ( Figure 1 and Figure 3 ), a state which is responsible for a chronic secretory phenotype that is generally considered pro-tumorigenic and promigratory, especially in GBM residual disease [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, LAV-BPIFB4 treatment downregulates senescence both in cancer cells in vitro and in T lymphocytes from GBM patients, a key event which may support a dual activity of LAV-BPIFB4 in the cancer microenvironment. We demonstrated that LAV-BPIFB4 can specifically counterbalance the therapy-induced senescence ( Figure 1 and Figure 3 ), a state which is responsible for a chronic secretory phenotype that is generally considered pro-tumorigenic and promigratory, especially in GBM residual disease [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Senescence is considered a favourable response to chemotherapy as it blocks tumoral cell proliferation. This view has been challenged as the irreversibility of drug-induced senescence remains under debate and the pro-tumorigenic properties of the senescent-associated secretory phenotype (SASP) are clearly demonstrated [ 52 , 53 ]. It has already been demonstrated that TMZ induces senescence rather than apoptosis in glioma cells [ 44 , 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that conditioned medium from aging astrocytes in vitro can promote the proliferation of glioma cell lines by increasing c-Myc; more importantly, this conditioned medium can improve the survival of TMZ-treated glioma cells 24 . Additionally, although residual glioma cells are very different from the original tumor, they secrete factors that are part of the aging-associated secretory phenotype (SASP), which maintains residual gliomas through therapy and drives drug resistance and recurrence 25 . Altogether, these results indicate that cellular senescence is likely to cause gliomas and residual tumors.…”
Section: Discussionmentioning
confidence: 99%